Frequent scanning using flash glucose monitoring contributes to better glycemic control in children and adolescents with type 1 diabetes - Tatsuhiko Urakami; Kei Yoshida; Remi Kuwabara; Yusuke Mine; Masako Aoki; Junichi Suzuki; Ichiro Morioka (Journal of Diabetes Investigation, 2022)
Abstract Aims/Introduction We examined the impact of scanning frequency with flash glucose monitoring on glycemic control in children and adolescents with type 1 diabetes. Materials and Methods The study included 85 patients, aged 14.0 ± 0.5 years, with type 1 diabetes. The median time in the target glucose range (TIR) and glycosylated hemoglobin (HbA1c) values were 50.0 ± 1.4% and 7.5 ± 0.1%, respectively. Results The median scanning frequency using flash glucose monitoring was 12.0 ± 0.4 times/day. Scanning frequency showed a significant positive correlation with TIR and an inverse correlation with HbA1c. Scanning frequency was identified to be the determinant of TIR and HbA1c by using multivariate analysis. The participants whose scanning frequency was <12 times/day were categorized as the low‐frequency group (n = 40), and those who carried out the scanning >12 times/day were categorized as the high‐frequency group (n = 45). Patients in the high‐frequency group were more likely to be treated with insulin pumps compared with those in the low‐frequency group; however, this difference was not significant (21.3 vs 5.3%, P = 0.073). The high‐frequency group showed significantly greater TIR than the low‐frequency group (57 ± 1.6 vs 42 ± 1.7%, P = 0.002). Furthermore, the high‐frequency group showed significantly lower HbA1c levels than the low‐frequency group (6.8 ± 0.1 vs 8.0 ± 0.1%, P < 0.001). Conclusions These findings showed that patients with a higher scanning frequency had better glycemic control, with greater TIRs and lower HbA1c levels, compared with those with a lower scanning frequency. Scanning frequency of >12 times/day might contribute to better glycemic outcomes in real‐world practice in children with type 1 diabetes.